From Hātobureiku to Ai Rabu Yū : English in Japanese popular music from the 1980s to the present - Tan, Hue Kay (2017)
This study seeks to chart the use of English in Japanese popular music through the analysis of 370 song titles and lyrics from 1980 to 2016 using Antconc. The study considers the history of Japanese popular music, as well as the linguistic and sociolinguistic status of English in Japan. The study then proceeds to identify and highlight a number of macro sociolinguistic trends of English use, as well as the use of orthographic scripts in Japanese popular music. Such trends include the development of code-switching from mainly intrasentential code-switches to both intrasentential and intersentential code-switches, the loanwords consisting mostly of nouns with wasei eigo or ‘Japan-made English’ becoming increasingly prevalent, as well as the shift from using hiragana and kanji to write English words to the use of katakana to write native Japanese lexicon. It is suggested that the analysis of song titles and lyrics in this report sheds light on the history of English use in Japanese popular music, and indicates future research areas related to the use of English in Asian popular music.